SSRI and Motor Recovery in Stroke: Reestablishment of Inhibitory Neural Network Tonus - Pinto, Camila B.; Saleh Velez, Faddi G.; Lopes, Fernanda; de Toledo Piza, Polyana V.; Dipietro, Laura; Wang, Qing M.; Mazwi, Nicole L.; Camargo, Erica C.; Black-Schaffer, Randie; Fregni, Felipe (Frontiers in Neuroscience, 2017)
Selective serotonin reuptake inhibitors (SSRIs) are currently widely used in the field of the neuromodulation not only because of their anti-depressive effects but also due to their ability to promote plasticity and enhance motor recovery in patients with stroke. Recent studies showed that fluoxetine promotes motor recovery after stroke through its effects on the serotonergic system enhancing motor outputs and facilitating long term potentiation, key factors in motor neural plasticity. However, little is known in regards of the exact mechanisms underlying these effects and several aspects of it remain poorly understood. In this manuscript, we discuss evidence supporting the hypothesis that SSRIs, and in particular fluoxetine, modulate inhibitory pathways, and that this modulation enhances reorganization and reestablishment of excitatory-inhibitory control; these effects play a key role in learning induced plasticity in neural circuits involved in the promotion of motor recovery after stroke. This discussion aims to provide important insights and rationale for the development of novel strategies for stroke motor rehabilitation.